2018
DOI: 10.3354/dao03196
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous mycobacteriosis in a captive Amazonian manatee Trichechus inunguis

Abstract: An adult male Amazonian manatee Trichechus inunguis under human care presented with 3 circular cutaneous lesions on the dorsal aspect of the rostrum and between the nostrils (plenum). Initially these lesions were superficial, hypopigmented, without warmth and non-painful. Microbiological cultures of skin swabs isolated Candida sp. and Pseudomonas aeruginosa, and topical treatment with antiseptic, antifungal, anti-inflammatory and antibiotic medication was instituted. This treatment strategy did not lead to any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Nonetheless, NTM have been known to infect animals such as chickens and quails (Meissner and Anz, 1977; Morita et al, 1999). Drug-susceptible M. fortuitum and M. abscessus were identified in a cutaneous lesion on the snout and nostrils of a captive Trichechus inunguis (manatee) in the Amazon (Reisfeld et al, 2018). In captive non-domesticated hoofed animals and in immunosuppressed dogs and cats, M. avium has been reported as disseminated disease (Thorel et al, 2004).…”
Section: Evidence For Animal and Insect Reservoirs For Ntm Associatedmentioning
confidence: 99%
“…Nonetheless, NTM have been known to infect animals such as chickens and quails (Meissner and Anz, 1977; Morita et al, 1999). Drug-susceptible M. fortuitum and M. abscessus were identified in a cutaneous lesion on the snout and nostrils of a captive Trichechus inunguis (manatee) in the Amazon (Reisfeld et al, 2018). In captive non-domesticated hoofed animals and in immunosuppressed dogs and cats, M. avium has been reported as disseminated disease (Thorel et al, 2004).…”
Section: Evidence For Animal and Insect Reservoirs For Ntm Associatedmentioning
confidence: 99%
“…data). Reisfeld et al (2018) also reported the treatment of Mycobacterium fortuitum and M. abscessus isolated from a persistent cutaneous lesion in the rostrum of an adult male Amazonian manatee with oral administration of ciprofloxacin and clarithromycin (6 mg/ kg), once daily for two months based on the antibiogram test in combination to other supportive drugs.…”
Section: Dietmentioning
confidence: 99%
“…Mab and other NTM subspecies are also commonly found in urban water plumbing and water systems, sometimes in symbiosis with Amoebae [18,19,20,21,22,23,24,25,26,27]. Moreover, Mab has been isolated from fish [28,29,30,31,32,33] and animals [34,35,36,37,38,39,40], who could also represent reservoirs for human infections. This makes exposure common and disinfection difficult, which is very problematic in healthcare settings [7,15,16,19,23].…”
Section: Possible M Abscessus Direct Transmission Among Cf Patientsmentioning
confidence: 99%